Brock biology of microorganisms - Brock, Thomas Dale, 1926-2021; Dunlap, Paul V., ....-; Madigan, Michael T., 1949-; Martinko, John M., 1947- (San Fransisco (Calif.) : Pearson/Benjamin Cummings, 2009)
Inhoudstafel: Unit 1: Principles of Microbiology 1) Microorganisms and Microbiology 2) A Brief Journey to the Microbial World 3) Chemistry of Cellular Components 4) Cell Structure and Function in Bacteria and Archaea 5) Nutrition, Culture, and Metabolism of Microorganisms 6) Microbial Growth Unit 2: Molecular Biology of Microorganisms 7) Essentials of Molecular Biology 8) Archaeal and Eukaryotic Molecular Biology 9) Regulation of Gene Expression 10) Overview of Viruses and Virology 11) Principles of Bacterial Genetics 12) Genetic Engineering 13) Microbial Genomics Unit 3: Microbial Diversity 14) Microbial Evolution and Systematics 15) Bacteria: The Proteobacteria 16) Bacteria: Gram-Positive and Other Bacteria 17) Archaea 18) Eukaryotic Cell Biology and Eukaryotic Microorganisms 19) Viral Diversity Unit 4: Metabolic Diversity and Microbial Ecology 20) Metabolic Diversity: Photography, Autotrophy, Chemolithotrophy, and Nitrogen Fixation 21) Metabolic Diversity: Catabolism of Organic Compounds 22) Methods in Microbial Ecology 23) Microbial Ecosystems 24) Nutrient Cycles, Bioremediation, and Symbioses Unit 5: Putting Microorganisms to Work 25) Industrial Microbiology 26) Biotechnology Unit 6: Antimicrobial Agents and Pathogenicity 27) Microbial Growth Control 28) Microbial Interactions with Humans Unit 7: Immunology 29) Essentials of Immunology 30) Immunology in Host Defense and Disease 31) Molecular Immunology Unit 8: Diagnosing and Tracking Infectious Diseases 32) Diagnostic Microbiology and Immunology 33) Epidemiology Unit 9: Microbial Diseases 34) Person-to-Person Microbial Diseases 35) Vectorborne and Soilborne Microbial Diseases 36) Wastewater Treatment, Water Purification, and Waterborne Microbial Diseases 37) Food Preservation and Foodborne Microbial Diseases
Includes index
Rev. ed. of: Brock biology of microorganisms / Michael T. Madigan. 11th ed. 2006
Pearson International Edition
Keywords: Microbiology; Medical microbiology